A Validation Study of the BRIEF-2 Among Kindergarteners and First Graders At-Risk for Behavior Problems. (January 2023) - Cumming, Michelle M.; Poling, Daniel V.; Qiu, Yuxi; Pham, Andy V.; Daunic, Ann P.; Corbett, Nancy; Smith, Stephen W.
Early identification of executive dysfunction and timely school-based intervention efforts are critical for students at risk for problematic behaviors during early elementary school. The original Behavior Rating Inventory of Executive Functioning (BRIEF) was designed to measure real-world behavioral manifestations of executive functioning, neurocognitive processes critical for school success. With the updated BRIEF-2, independent validation is needed with kindergarten and first grade students at risk for emotional and behavioral disorders. Thus, using item level analyses, we examined the factor structure of the BRIEF-2 Teacher Rating form with 1, 112 students. Results indicated little evidence for the original three-index model and supported a modified two-index model, with a Cognitive Regulation Index and an overall Behavior–Emotion Regulation Index. Criterion related validity indicated positive relationships with performance-based executive functioning (Head-Toes-Knees-Shoulders) and later internalizing and externalizing behaviors. We discuss implications of findings for early identification and school-based intervention efforts, as well as future research.